Effects of the rotor pedalling system on the performance of trained cyclists during incremental and constant-load cycle-ergometer tests - Lucia, A.; Balmer, J.; Davison, R. C. R.; Perez, M.; Santalla, A.; Smith, P. M. (International Journal of Sports Medicine, 2004)
The aim of this study was to determine the effects of Rotor, a new cycle crank configuration that effectively allows the pedals to move independently throughout the duty cycle, on indices of endurance cycling performance in trained cyclists. Ten cyclists (5 Rotor users and 5 non-users; age (mean +/- SD): 22 +/- 5 y; VO2max: 69.5 +/- 5.1 mL / kg-1 / min-1) volunteered to participate in the study. On four separate days, the subjects performed four cycle-ergometer tests, i.e. two incremental tests and two 20-min tests. An imposed crank rate of 75 rev . min-1 was used during all tests. The incremental protocol started at 112.5 W, and the power output was increased by 37.5 W every 3 min until volitional exhaustion. The 20-min tests were performed at a fixed power output equivalent to 80 % of the highest power output that the cyclists maintained for a complete 3-min period during incremental tests. Both types of tests were performed with the conventional crank system and the Rotor following a counter-balanced, cross-over design. Gas exchange parameters were measured in all the tests and blood lactate was determined at the end of each 3-min period (incremental tests) and at the end of the 20-min tests. A three factor (pedalling system used during the tests x habitual pedalling system x power output [incremental tests] or time [20-min tests]) ANOVA with repeated measures on power output (incremental tests) or time (20-min tests) was used to analyse several indices of performance, e.g. peak power output, VO2max, lactate threshold, onset of blood lactate accumulation, economy, delta, and gross efficiency. No differences (p > 0.05) were found between the Rotor and conventional systems for any of the aforementioned variables. It seems that the theoretical advantage brought about by the Rotor system, i.e. improved contra-lateral cooperation of both legs, would be minimized in trained cyclists. Although field studies are needed to assess the possible implications, in terms of actual racing, of the new system, commonly used indicators of endurance cycling performance do not seem to be improved with the Rotor in trained cyclists.